Growth hormone secreting pituitary carcinomas: Case report and review of literature. (October 2021) - Vekaria, Shivani; Chen, Fei; Zan, Elcin; William, Christopher; Sen, Chandra; Lebowitz, Richard; Zagzag, David; Warren, Floyd A.; Brandler, Tamar C.; Agrawal, Nidhi
Abstract: Objective: Pituitary carcinoma is a rare tumor, defined as a tumor of adenohypophyseal cells with systemic or craniospinal metastasis. We present a case of a growth hormone (GH)-secreting pituitary carcinoma with a review of literature to better characterize this disease. Design: Case report and literature review of 25 cases of GH-secreting pituitary carcinomas Results: The age of diagnosis of GH-secreting carcinomas ranged 24–69 years old with a mean age of 44.4 with 52% of cases present in females. Mean latency period between diagnosis of acromegaly and transition to pituitary carcinoma was 11.4 years with mean survival being 3.4 years. Conclusion: Growth hormone (GH)-secreting pituitary carcinomas are rare and hard to distinguish from aggressive pituitary adenomas. From review of literature, treatment options include debulking surgery, radiotherapy, or chemotherapy with dismal outcomes. There are no diagnostic markers or features which can predict metastatic progression of these tumors. Future studies with genomic landscapes and relevant tumor markers are needed to identify pituitary tumors most likely to metastasize. Highlights: A rare case of a growth hormone-secreting pituitary carcinoma Genetic markers that help identify pituitary carcinoma Limited treatment modalities for pituitary carcinoma Future studies of targeted therapies are needed.